Effectiveness of child sexual abuse prevention programs on knowledge acquisition: A meta-analytical study - Cerezo-Guzmán, María Victoria; Ferragut-Ortiz-Tallo, Marta; Ortiz-Tallo-Alarcón, Margarita; Rodríguez-Fernandez, Raquel (Elsevier, 2023)
Background: Child sexual abuse (CSA) is a type of maltreatment considered a global health problem. CSA is a traumatic experience with important consequences for the victim’s health. It is essential to report the effectiveness of CSA prevention programs to offer society useful tools to combat this abuse. Objective: We aimed to study the effectiveness of CSA prevention programs on the knowledge acquisition based on comparing pre- and post-treatment changes, and also if their effectiveness is related to program-related and methodological variables. Participants and settings: Standardised mean change (with studies that report pre-post program measures) of the effectiveness of CSA prevention programs published between 2014 and 2021 was carried out. Methods: The general effectiveness of these programs and whether the results were influenced by program-related variables (the duration, the target population, participants’ age, or the type of intervention) or by methodology-related factors (the agent who taught them, the geographical area where they were carried out or the way the programs were evaluated) were analysed. A total of 43 samples analysing knowledge about CSA as a dependent variable were included. Results: The results reported a combined effect size considered large (dMR = 0.96, 95 % CI [ 1.10, 0.82], p < .001). High inter-study heterogeneity was observed in the meta-analysis, although only the geographic area where the studies were conducted appears as a significant moderator. Conclusions: In conclusion, the prevention programs included in this analysis significantly improved the participants’ knowledge acquisition
Keywords: Niños -- Abusos sexuales -- Prevención; Eficacia organizacional; Delitos sexuales; Niños -- Psicología; Prevention programs; Effectiveness; Child sexual abuse; Abuse and trauma; Meta-analysis